(untitled) (aSSIST Business Review, 2026)
(1) Background/Purpose: Korea’s white paperboard (folding boxboard) industry faces a compounding crisis: domestic and global supply surpluses driven by large-scale capacity additions in Southeast Asia (notably XSD International Paper’s 350,000 t/y Malaysia facility in 2022), intensifying export-market competition, rising raw material costs, tightening environmental regulation including the EU Carbon Border Adjustment Mechanism (CBAM), and accelerating digital transformation. This study seeks to identify evidence-based strategic responses that can enable Korean paperboard firms to move from crisis management to sustainable competitive growth. (2) Methodology: The study combines systematic environmental analysis (PEST, Porter’s Five Forces, market sizing), industry data from the Korea Paper Association and international sources (PMI, Fisher International, SCI Verkehr), and four in-depth innovation case studies: Company A’s fly ash recycling and CO₂ carbonation technology; Company B’s sterilized-pack circular economy model; Stora Enso’s biomass-based Formed Fiber technology and intelligent manufacturing system; and Metsä Board’s Excellence Centre 2030 digital-circular integration program. (3) Findings: Despite structural pressures, four transformative growth pathways are identified. First, waste-to-resource innovation: Company A’s fly ash recycling reduced waste disposal costs by 50% and enabled domestic PCC production with CO₂ capture; Company B’s sterilized-pack recycling achieved 100% circular valorization of pulp and polyAl layers, establishing a customer lock-in model. Second, renewable materials market creation: Stora Enso’s Formed Fiber generated EUR 280M in Q3 2023 revenue (+35% YoY), secured by long-term contracts of EUR 400M/year to 2025. Third, AI-driven manufacturing intelligence: Stora Enso’s IMS (2,000+ sensors, digital twin, AI quality prediction) reduced defect rates by 32%, improved energy efficiency by 24%, and saved EUR 12M/year; Metsä Board’s predictive quality management reduced defects by 47% and raised customer satisfaction by 18%. Fourth, circular-by-design partnerships: Metsä Board’s Circular Design program and water recycling system achieved 99% product recyclability and 15% water cost reduction. (4) Originality/Value: This study provides the first integrated strategic analysis linking Korean paperboard industry structural challenges to both domestic innovation cases and Nordic benchmark practices, producing a multi-horizon strategic framework covering technology innovation, new market entry, cost competitiveness, digital transformation, and human resource development.